Long-term alteration of the hypothalamic-pituitary-adrenal axis in children undergoing cardiac surgery in the first 6 months of life. (3rd September 2017) - McGauran, Monica; Jordan, Brigid; Beijers, Roseriet; Janssen, Irma; Franich-Ray, Candice; de Weerth, Carolina; Cheung, Michael
Abstract: Children with congenital heart disease (CHD) have poorer neurodevelopmental and psychological outcomes. The mechanisms underlying this remain unclear. One mechanism could be that the stressful experience of cardiac surgery early in life influences long-term hypothalamic–pituitary–adrenal (HPA) axis regulation. Dysregulation of the HPA axis has been linked to poorer neurocognitive and psychological outcomes in other study populations. This case–control study aims to compare HPA-axis regulation (circadian rhythm and reactivity) using salivary cortisol in 3- to 5-year-olds with CHD who did and did not have cardiac surgery prior to 6 months of age. Saliva samples for cortisol analysis were collected from preschoolers with CHD ( N = 28, Males = 18, Females = 10) over two weekend days, and before and after an echocardiogram. Caregiver education, child age, sex, and cardiac disease severity score were included as confounders. Multilevel analysis (hierarchical linear modeling) was used to analyze the data. The analysis for the cortisol circadian rhythm shows that the early surgery group has a flatter diurnal slope secondary to lower mean weekend morning waking cortisol levels than controls but similar mean bed time values. Multilevel analysis of the stress response to an echocardiogram indicates that the early surgery group has an increased response when compared to the control group. This is the first study to show that cardiac surgery prior to 6 months of age is associated with a different pattern of HPA-axis regulation at 3–5 years of age.